First Record of Chrysomya rufifacies (Macquart) (Diptera, Calliphoridae) in Southeastern Brazil - Ribeiro, Antonia de Castro; Cardoso, Debora; Lessa, Cláudia Soares dos Santos; Moya-Borja, Gonzalo Efrain; Aguiar, Valéria Magalhães (EntomoBrasilis, 2013)
The present note reports the first record of Chrysomya rufifacies (Macquart) in Southeastern Brazil, in the municipality of Seropédica, Rio de Janeiro. The collecting was conducted with Diptera traps using fresh fish as bait. Primeiro Registro de Chrysomya rufifacies (Macquart) (Diptera, Calliphoridae) no Sudeste do Brasil Resumo. A presente nota relata o primeiro registro da espécie Chrysomya rufifacies (Macquart), no Sudeste do Brasil, no Município de Seropédica, Rio de Janeiro. As coletas foram realizadas com auxílio de armadilhas para dípteros e a isca utilizada foi peixe fresco.